The Cumulative Impact of Health Adversities on Children's Later Academic Achievement. - Nguyen, Cattram; Wake, M; Wake, Melissa; O'Connor, Meredith; Quach, J; Quach, Jon (My University, 2017)
OBJECTIVE: We aimed to determine whether the accumulation of physical, psychosocial and combined health adversities measured at age 8-9 years predicts worsening of academic scores cross-sectionally at 8-9 and longitudinally at 10-11 years. METHODS: Design: Longitudinal data from Waves 3 and 4 in the Longitudinal Study of Australian Children (83% of 4983 retained). Exposures (8-9 years): Physical health adversities (yes/no; summed range 0-5): overweight, special health care needs, chronic illness, PedsQL Physical, global health. Psychosocial health adversities (yes/no; summed range 0-4): parent- and teacher-reported behavior, PedsQL Psychosocial, sleep problems. Combined health adversities (range 0-9). Outcomes (8-9, 10-11 years): National academic standardized test scores. ANALYSIS: Generalized estimating equations, accounting for multiple academic domains in each year and socioeconomic position and cognition. RESULTS: At 8-9 years, 23.9%, 9.9% and 5.3% had 1, 2 or ≥3 physical health adversities, respectively, while 27.2%, 9.5% and 4.9% had 1, 2 or ≥3 psychosocial health adversities, respectively. For each additional health adversity at 8-9 years, academic scores fell incrementally in Year 3 and Year 5 (both p<0.001), with reductions of at least 0.4 standard deviations for ≥3 health adversities. Number was more important than type (physical, psychosocial) of adversity. CONCLUSION: The accumulation of health adversities predicts poorer academic achievement up to 2 years later. Interventions may need to address multiple domains to improve child academic outcomes and delivered across the health-education interface.
Keywords: Children -- School age; Health -- Physical; Health -- Mental; Health and wellbeing; Health; Children; Physical; School age; Mental; Health and wellbeing